Resilience of Nursing Undergraduate (S1) Students Living Away from Home - Rismanudin, Rismanudin (Jurnal Penelitian Perawat Profesional, 2025)
The ability of migrant students to cope with stress, overcome obstacles, and recover from failure in an academic environment is known as resilience. In the field of nursing, academic resilience plays an important role because it can help students conquer complex learning challenges while improving student welfare. Objective: This study aims to delve deeper into academic resilience in Undergraduate (S1) Nursing students. Design: This study uses a qualitative approach with a case study method. Sampling was carried out purposively, and data analysis used the Amedeo Giorgi method. Results: This study identified several main themes, namely: 1) Various psychological responses such as feelings of happiness, stress, and boredom experienced by students during lectures, 2) Difficulties in managing time when facing lecture activities, and 3) Time management and increased sense of responsibility as a form of effort in facing the challenges of preparing a thesis. Conclusion: The resilience of regional students has a crucial role in supporting the academic achievement and welfare of S1 nursing students. Understanding the factors that affect academic endurance and designing appropriate interventions can help students better cope with the challenges of their studies, thereby increasing the chances of successful studies. Further research is needed to explore more detailed and effective strategies to strengthen the resilience of undergraduate nursing students who migrate.